Exponential weak Bernoulli mixing for Collet-Eckmann maps - Keller, Gerhard (Israel Journal of Mathematics, 1994)
We prove exponential weak Bernoulli mixing for invariant measures of certain piecewise monotone interval maps studied in [BK] and [KN]. In particular we prove this for unimodal maps with negative Schwarzian derivative satisfying lim<span class="MathJax" data-mathml="liminfn→∞<mroot>|DTn(Tc)|n</mroot>>1" id="MathJax-Element-1-Frame" role="presentation" style="position: relative;" tabindex="0">liminfn→∞|DTn(Tc)|−−−−−−−−−√n>1, wherec is the unique critical point ofT.